Is India Fit for a Role in Global Governance? The Predicament of Fragile Domestic Structures and Institutions - Herbert Wulf (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2014)
How do emerging powers cooperate at the global level? The government of India-one such power-has let it be known that it is seeking an enhanced role in global governance. Is Indian society ready for this new, global role? This paper analyses the impact of domestic factors on India's foreign-policy ambitions. It begins by examining the country's paradoxical social and economic development and the problems it faces in the realm of internal security. Section 2 looks at a number of socio-cultural and political factors that may help to explain India's new, globally oriented approach to foreign policy: 1. Indian society's capacity to merge tradition and modernity, resulting in the creation of resilient institutions; 2. the amorphous nature of Indian society and its distinctive capacity to exploit vagueness and improvisation in resolving problems; and 3. the competition and cooperation between political actors at national and federal level, which has resulted in the emergence of a functioning federal system but has also complicated centre-state relations. The paper concludes that, overall, the question of whether India's social structures and political institutions are robust enough to allow it to assume a global role is not one that can be answered unambivalently. The government has undertaken major reforms and the country's institutions are strong, resilient, adaptive, and keen on global cooperation. On the other hand, Indian society is still bedeviled by incoherent economic development in which phenomenal growth is found alongside appalling poverty and inequality.
urn:nbn:de:hbz:464-20150105-101521-7
Keywords: 320; Conflict; development; domestic structures; economic growth; federalism; foreign policy; global governance; hybridity; India; internal security; poverty; socio-economic development; regionalism; resilient institutions; soft power; tradition and modernity